Eco-Entrepeneurs of Tomorrow: Green Innovation For Contribution In Sustainable Development - Diyan Agus Permana (Publication of the International Journal and Academic Research, 2024)
In the contemporary discourse of sustainable development, the emergence and significance of eco-entrepreneurs stand as pivotal drivers of green innovation. Marketing strategies no longer solely emphasize aspects like quality, price, and benefits but also emphasize environmental sustainability and social responsibility, thus enabling industries to pursue sustainable development. The primary aim of this research is to investigate the contribution of ecological entrepreneurship through green innovation in achieving sustainable development. Methodology in this research using literature review which serves as the backbone for understanding the dynamics of eco-entrepreneurship and green innovation for contribution in sustainable development. Through a comprehensive literature review, the research examines existing theories, case studies, and empirical evidence related to eco-entrepreneurship, green innovation, and sustainable development. The literature review method allows for an in-depth analysis of the various strategies and innovations employed by eco-entrepreneurs to reduce environmental impact while maintaining economic viability. The study emphasizes the vital role of green innovation importance in driving sustainability, exploring how society responds to green innovations, green innovation contributions to sustainable development, and also the green innovation business models that incorporate green practices. It highlights the interconnectedness of technological advancements, public acceptance, and strategic business approaches in fostering a sustainable and eco-friendly future.